Degranulation of rat omental mast cells by A1 receptor agonists in vitro - A. M. Northover; B. J. Northover (Mediators of Inflammation)
The haemodynamic effects of adenosine are thought to result in part from a release of mast cell amines via A3 receptor stimulation. To investigate the nature of the receptors involved in adenosine-induced mast cell degranulation in the rat isolated omentum we have used adenosine analogues with varying specificities as activators of the A1, A2 and A3 receptors, and antagonists with differing specificities for A1 and A2 receptors. Analogues which act predominantly as A1 (e.g. N6-cyclopentyladenosine) or as mixed A1/A2 receptor agonists (e.g. adenosine, inosine, 5'-(Nethylcarboxamido) adenosine) caused mast cell degranulation, whereas a predominantly A3 receptor agonist (IB-MECA) was inactive. Pre-treatment of the omentum with the A1/A2 receptor antagonist 8-phenyltheophylline or with the more specific A1 receptor antagonist 8-cyclopentyl-1,3-dipropylxanthine significantly reduced agonist-induced degranulation. Pre-treatment with disodium cromoglycate or with BN52021 also reduced degranulation of mast cells in response to N6-cyclopentyladenosine. In the rat isolated omental mast cell we conclude that degranulation is an indirect result of A1 receptor stimulation. Platelet-activating factor release appears to mediate at least part of the degranulation.